2023
DOI: 10.3389/fpsyg.2022.1104073
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Team Learning Climate on Innovation Performance – Mediating role of knowledge integration capability

Abstract: To address the fierce competition for corporate innovation in the digital economy, this study introduces knowledge integration capability as a mediating variable in light of social information processing theory, and explores the mechanism of team learning climate on innovation performance. Data were collected from a sample of 184 team members for statistical analysis, and Statistical methods such as descriptive statistical analysis, correlation analysis, and regression analysis were used to verify the study hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Moreover, the results show that knowledge integration capability mediates the domestic and international external collaboration-SMEs' NPD performance relationships. These findings support the existing literatures which found that collaboration activities and open innovation activities contribute to the improvement of knowledge integration capability [12][13][14] and knowledge integration capability can promote NPD and innovation performance [15,71,72]. In addition, the results indicate that organizational legitimacy strengthens the positive impacts of domestic and international external collaboration on SMEs' NPD performance.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the results show that knowledge integration capability mediates the domestic and international external collaboration-SMEs' NPD performance relationships. These findings support the existing literatures which found that collaboration activities and open innovation activities contribute to the improvement of knowledge integration capability [12][13][14] and knowledge integration capability can promote NPD and innovation performance [15,71,72]. In addition, the results indicate that organizational legitimacy strengthens the positive impacts of domestic and international external collaboration on SMEs' NPD performance.…”
Section: Discussionsupporting
confidence: 88%
“…The third limitation is that the data is gathered from Hong Kong, so the conclusions and implications are solely applicable to the region (Guo et al , 2020; Li et al , 2023). This is the limitation that applies to all geographically restricted research designs (Huang et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Huawei has improved work efficiency and quality through the refined design and standardized management of various business processes. Huawei has established a comprehensive process management system, including process specification, process evaluation, and process improvement, which improves the speed and effectiveness of innovation by continuously optimizing processes [16].…”
Section: Process Optimizationmentioning
confidence: 99%
“…Huawei realizes the sharing and collaborative use of resources through cross-departmental integration. Huawei encourages cooperation and coordination between different departments and promotes crossdepartmental integration of resources in order to improve the efficiency of resource utilization and the comprehensive capability of innovation projects [20].…”
Section: Resource Allocationmentioning
confidence: 99%